MODIFICATION OF THROTTLE, ENGINE STOP, AND DATA INPUT MECHANISM SYSTEM IN ELEVATION SYSTEM, AND ROTARY CANON TANK AMX 10 PAC 90 USING CAMERA SENSOR - Ayip Rivai Prabowo; Dueng Deriva; Endro Prasetijoadi; Sigit Bangun S (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Along with technological developments in the industrial revolution era 4.0 military technology is required to beable to adjust to the development of human resources or defense equipment. Research that has been donepreviously is that the Throttle manually changed using Throttle with DC motor drive, there are somedisadvantages caused by using a DC motor, among others, it is difficult to map the direction and speed of themotor so it is difficult to drive, the same as that used as an engine mover Stop that is by using a DC Type Motorwhile for the input system of rotary and elevation is still manually operated by the remote controller operator.From the debate that occurred the author will make modifications to the throttle system that uses a DC wipermotor in exchange for using an angle motor can be easily, for the engine Stop the same system that is initiallyusing a DC wiper motor is replaced using a servo motor so that the mapping angle of 0 degrees to 90 degreescan be easily mapped, while for elevation and rotary canon by inputting data with the camera module using thecamera sensor as for microcontroller data inputKeywords: Stop Engine, dc motor